The effectiveness of video usage as teaching materials for online learning / Haslinda Noradzan ...[et al.] - Noradzan, Haslinda; Ahmad Zaini, Azniza; Abu Bakar, Noridah; Rashid, Zarina Zainul (2016)
This paper investigates the effectiveness of video usage as teaching materials to support online learning activities in Universiti Teknologi MARA. Nowadays, the online learning has become a common method for teaching especially in higher institutions in Malaysia. With the development of Internet and Web 2.0 for education, conducting teaching and learning activities become a challenging task since students have different learning preferences and the lecturers must be well-prepared in constructing teaching materials by utilizing the available tools. Hence, it is vital for the academicians to explore on methods to conduct online classes in attractive and meaningful way for their students. This study was conducted using quantitative approach whereby it involved three groups of diploma students. The respondents for this study were 120 students of Diploma in Computer Science that took two different computer science courses and 40 students of Diploma in Sport Science that registered for IT Essential for Sports course. Three sets of videos containing the learning objectives for three different courses were distributed to the students through i-Learn portal during their online class. Questionnaires were distributed one week after the videos were viewed by the students to examine their acceptance towards the new approach and the effectiveness of learning using videos. The findings suggested that there was a significant difference between male and female students on accepting the video as teaching materials although the number of female students was greater than male. The students were also able to adapt various types of learning materials gradually since most of them are computer and Internet literate.